The Study of Land Use/Land Cover in Chunar Tehsil, Mirzapur District using Landsat Data - Verma, Narender (National Geographical Journal of India, 2022)
In this paper an attempt has been made to analyse Land use/Landcover change in Chunar Tehsil of Mirzapur District in Uttar Pradesh using Geospatial technology.Land is becoming a scarce resource due to immense agricultural and demographic pressure. Hence, information on land use/land cover and possibilities for their optimal use is essential for the selection, planning and implementation of land use schemes to meet the increasing demands for basic human needs and welfare. In the present study two scenes of freely available Landsat 5 and Landsat 8 (TM and OLI-TIRS) data of path and row 142/43 for the years 1991 and 2013 have been used.Supervised classification with maximum likelihood classifier has been performed to delineate the different landuse/landcover classes in the study area. In all six classes viz. agricultural land, built up land, dense forest, scrub, water body and barren land have been identified. The study shows sporadic changes in the land use land cover of the study area between 1991 and 2013. There has been a substantial decline in area under forest, scrub and barrenland. Most of it has been converted either into built up land or agriculture. This can be attributed to the sporadic growth of population and resulting expansion of agricultural activities